Molecular Simulations Reveal the Role of Antibody Fine Specificity and Viral Maturation State on Antibody-Dependent Enhancement of Infection in Dengue Virus - Ripoll, Daniel R.; Wallqvist, Anders; Chaudhury, Sidhartha (Frontiers in Cellular and Infection Microbiology, 2019)
Recent clinical studies have revealed that severe symptoms of dengue fever are associated with low pre-existing antibody levels. These findings provide direct clinical evidence for the theory of antibody-dependent enhancement of infection (ADE), which postulates that sub-neutralizing levels of antibodies facilitate the invasion of host cells by the dengue virus. Here, we carried out molecular simulations of polyclonal antibody mixtures binding to the dengue virus particle to explore the contributions of antibody concentration, epitope specificity, and viral maturation to ADE in the context of primary and secondary dengue infections. Our simulation results reproduced in vitro studies of ADE, providing a molecular basis for how sub-neutralizing antibody concentrations enhance the ability of the virus to infect host cells. We found that antibody fine specificity, or the relative antibody response to different epitopes on the surface of the dengue virus, plays a major role in determining the degree of ADE observed at low antibody concentrations. Specifically, we found that the higher the relative antibody response to certain cross-reactive epitopes, such as the fusion loop or prM, the greater was the range of antibody concentrations where ADE occurred. This potentially explains why low antibody concentrations are associated with severe disease in secondary infections. Further exploration of the role of viral heterogeneity in ADE revealed that our observations were robust to a wide range of dengue virus conformations, and that partially mature states, in particular, are associated with the greatest degree of ADE.